From Smart Apes to Human Brain Boxes. A Uniquely Derived Brain Shape in Late Hominins Clade - Melchionna, Marina; Profico, Antonio; Castiglione, Silvia; Sansalone, Gabriele; Serio, Carmela; Mondanaro, Alessandro; Di Febbraro, Mirko; Rook, Lorenzo; Pandolfi, Luca; Di Vincenzo, Fabio; Manzi, Giorgio; Raia, Pasquale (Frontiers in Earth Science, 2020)
Modern humans have larger and more globular brains when compared to other primates. Such anatomical features are further reflected in the possession of a moderately asymmetrical brain with the two hemispheres apparently rotated counterclockwise and slid anteroposteriorly on one another, in what is traditionally described as the Yakovlevian torque. Developmental disturbance in human brain asymmetry, or lack thereof, has been linked to several cognitive disorders including schizophrenia and depression. More importantly, the presence of the Yakovlevian torque is often advocated as the exterior manifestation of our unparalleled cognitive abilities. Consequently, studies of brain size and asymmetry in our own lineage indirectly address the question of what, and when, made us humans, trying to trace the emergence of brain asymmetry and expansion of cortical areas back in our Homo antecedents. Here, we tackle this same issue by studying the evolution of human brain size, shape, and asymmetry on a phylogenetic tree including 19 apes and Homo species, inclusive of our fellow ancestors. We found that a significant positive shift in the rate of brain shape evolution pertains to the clade including modern humans, Neanderthals, and Homo heidelbergensis. Although the Yakovlevian torque is well evident in these species and levels of brain asymmetry are correlated to changes in brain shape, further early Homo species possess the torque. Even though a strong allometric component is present in hominoid brain shape variability, this component seems unrelated to asymmetry and to the rate shift we recorded. These results suggest that changes in brain size and asymmetry were not the sole factors behind the fast evolution of brain shape in the most recent Homo species. The emergence of handedness and early manifestations of cultural modernity in the archeological record nicely coincide with the same three species sharing the largest and most rapidly evolving brains among all hominoids.